2003
DOI: 10.1902/annals.2003.8.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Periodontal Disease and Risk for Atherosclerosis, Cardiovascular Disease, and Stroke. A Systematic Review

Abstract: 1. Periodontal disease may be modestly associated with atherosclerosis, MI, and CVD. 2. Additional large-scale longitudinal epidemiologic and intervention studies are necessary to validate this association and to determine causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
321
1
18

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(345 citation statements)
references
References 40 publications
5
321
1
18
Order By: Relevance
“…At the very least, inflammatory markers measured by OMT reflect peripheral, localized inflammation in the mouth, a critical site for immune response, as it is a primary avenue by which bacteria and viruses can enter and infect the body. Moreover, oral inflammatory activity is also implicated in the pathogenesis of periodontal disease (61), which is linked to other systemic disease including diabetes and cardiovascular diseases (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…At the very least, inflammatory markers measured by OMT reflect peripheral, localized inflammation in the mouth, a critical site for immune response, as it is a primary avenue by which bacteria and viruses can enter and infect the body. Moreover, oral inflammatory activity is also implicated in the pathogenesis of periodontal disease (61), which is linked to other systemic disease including diabetes and cardiovascular diseases (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism(s) responsible for the hyperinflammatory neutrophil phenotype seen in chronic periodontitis (the commonest form of the disease) is currently unknown, although analyses indicate that it is not a result of altered adhesion molecule (7) or Phox gene (10) expression, polymorphisms in Fc␥R (8,12), or in vitro priming by cytokines or LPS (13,14). Furthermore, the association of periodontitis with increased relative risk for cardiovascular disease, fatal coronary events (15), and ischemic stroke (16), and the demonstrable medium-term reductions in vascular endothelial dysfunction following aggressive periodontal therapies (17), emphasize the potential impact of inflammatory periodontitis on peripheral macrovascular disease.…”
Section: P Eripheral Blood Neutrophils (Pbn)mentioning
confidence: 99%
“…It has been reported that 10% to 15% of the periodontal patients had been linked to CVD. [17][18][19] We previously showed that periodontopathic pathogens deteriorated ventricular remodeling after MI 20,21) and other cardiovascular diseases. [22][23][24][25][26] However, a detailed mechanism is still to be elucidated.…”
mentioning
confidence: 99%